Binding of Polycyclic Aromatic Hydrocarbons to Polyadenylic Acid - Craig, A. Morrie (1970)
A number of polycyclic aromatic hydrocarbons bind to the double-stranded, acid form of polyadenylic acid (poly A). Model building shows that these hydrocarbons may intercalate in the helix, and be well protected from contact with the aqueous medium. Hydrocarbons that are too large to be so protected are found not to bind. A size criterion for the binding of hydrocarbons to poly A therefore exists. This criterion differs from one that was previously found for DNA. The size criteria for DNA and poly A, together, serve as strong evidence for the intercalation model for hydrocarbon complexes. Model-building experiments show that only a small portion of the hydrocarbon need extend into the medium to prevent binding. This finding implies that in two cases (1,2,5,6-dibenzanthracene·poly A and 3,4-benzpyrene·DNA) the structure of the complex is almost completely determined by the size criterion alone.